PERTANGGUNGJAWABAN NEGARA TERHADAP PENCEMARAN LAUT TIMOR OLEH TUMPAHAN MINYAK AUSTRALIA BERDASARKAN UNCLOS III 1982 DAN HUKUM LINGKUNGAN INTERNASIONAL - Novia Kusma Ningsih; Mexsasai Indra; Widia Edorita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Border management state of work never ending since that state born. This is thing based of state constitution one of state ,except country, government, and ability to interaction with international world and there is recognition of other countries. Contamination of path be important trauble to indonesian, because has contamination sea of indonesia until exclusive economic zone. Base philosophical based in article 192 United Nations Convention on the Law of The Sea (UNCLOS) 1982, that every country should keep of the sea, and that mean is article give pressed that ecosystem of sea is a part should to keep and long lasting for every countries. Research purpose is first about dispute resolution in international law that use as method to dispute settlement cases contamination of the sea timor; and second state responsibility of explode examination into sea timor.As for result is first, dispute resolution that taken during this among parties involved into dispute that is, Indonesia and PTTEP Australasia is diplomacy. Second, form of responsibility among australia, and indonesia is in the case of tort claim and compensation.